STRATEGI BAURAN PEMASARAN SAYURAN DALAM MENINGKATKAN MINAT BELI KONSUMEN - Rofinus Kanisius Wangge; Sarlina Noni (Program Studi Agribisnis, Fakultas Pertanian, 2021)
The purpose of this study is to look at the implementing of marketing mix of vegetbles from Agriculture Faculty University of Nusa Nipa in increasing consumer buying interest. The results of the study: consumers have different abilities in mentioning the characteristics or attributes of these products. Consumers try to satisfy a need by implementing a marketing mix for buying interests :1). Organic vegetable products located in the Garden faculty of agriculture, University of Nusa Nipa, very diverse, namely: onion, cayenne pepper, tomato, papaya, watermelon, cucumber, mustard and kale. Diverse products greatly influence consumer interest because the product has many health benefits, this is very attractive for consumers who will decide to buy and consume the product they want, 2). The specified price or sales price of vegetable products can be reached by consumers or housewives, buying at an affordable price but has great benefits, for yourself, family communities and life. 3). the location of the garden is very strategic, located on the side of the road and easily reachable to customers or consumers. 4). Promoting Organic Vegetables is done either orally or in writing also through whats App and facebook. Keywords : marketing mix, consumer buying interests The purpose of this study is to look at the implementing of marketing mix of vegetbles from Agriculture Faculty University of Nusa Nipa in increasing consumer buying interest. The results of the study: consumers have different abilities in mentioning the characteristics or attributes of these products. Consumers try to satisfy a need by implementing a marketing mix for buying interests :1). Organic vegetable products located in the Garden faculty of agriculture, University of Nusa Nipa, very diverse, namely: onion, cayenne pepper, tomato, papaya, watermelon, cucumber, mustard and kale. Diverse products greatly influence consumer interest because the product has many health benefits, this is very attractive for consumers who will decide to buy and consume the product they want, 2). The specified price or sales price of vegetable products can be reached by consumers or housewives, buying at an affordable price but has great benefits, for yourself, family communities and life. 3). the location of the garden is very strategic, located on the side of the road and easily reachable to customers or consumers. 4). Promoting Organic Vegetables is done either orally or in writing also through whats App and facebook. Keywords : marketing mix, consumer buying interests